Comparative Evaluation of the Effectiveness of PowerPoint and Chalk and Talk Method of Dental Health Education on Knowledge, Practices, and Oral Health Status of 12–15-year-old Tribal Schoolchildren of a District in Maharashtra - A Community-based Trial - Saurabhachandra B. Pawar; Vittaldas Shetty; Chaitanya S. Buddhikot; Utkarsha V. Deshpande; Rasika B. Pawar (Journal of Indian Association of Public Health Dentistry)
Introduction: Periodontal disease is a major public health problem that challenges health systems around the world and largely goes unnoticed by patients until it reaches an advanced stage. Schools remain an important setting where the children’s skills are developed and resistant to change, so it is efficient and effective to reach out to the children, families, and community members. Aim: This study aims to assess the effectiveness of two different modes of oral health education (OHE) among tribal schoolchildren of the adolescent age and to determine the most effective mode among them. Methodology: This randomized controlled trial involved 185 participants in each group employed by cluster random sampling and randomized by the lottery method. Gingival and plaque indices were used to measure the periodontal status at baseline, 1st, 2nd, and 3rd months where Group A received OHE by PowerPoint presentation and Group B received chalk and talk method. Descriptive statistics, repeated measure analysis of variance, and Chi-square test were used for data analysis using SPSS version 19.0. Results: A statistically significant decrease in the gingival and plaque index scores was observed postintervention with PowerPoint presentation compared to the chalk and talk method with a significant increase in the oral health knowledge in both groups. Conclusion: School-based OHE is effective in improving oral hygiene knowledge, attitude, and practices that lead to better plaque control and better improvement in gingival health.